Embryo reintroduction to enhance genetic diversity in a Marsh deer population: first attempt, outcomes, challenges, and future perspectives - Galindo, David Javier; Peres, Pedro Henrique de Faria; Zanetti, Eveline dos Santos; de Oliveira, Márcio Leite; Rola, Luciana Diniz; Duarte, José Maurício Barbanti (Frontiers in Conservation Science, 2025)
IntroductionThe loss of genetic diversity is a critical factor in the extinction process, exacerbated by anthropogenic pressures and demographic stochasticity, particularly in small populations. Traditional population restoration methods, such as individual translocation and ecological corridors, present challenges, including high costs, adaptation difficulties, pathogen introduction, and outbreeding risks. Embryo reintroduction has emerged as a potential strategy for genetic rescue. This study aimed to evaluate the feasibility of embryo transfer as a genetic rescue tool in the marsh deer (Blastocerus dichotomus), a species classified as Vulnerable by the IUCN.MethodsFollowing the construction of the Sérgio Motta Hydroelectric Power Plant (UHSM) in 1998, a population of over 1,000 marsh deer was impacted, leading to the capture of 93 individuals for ex situ (82) and in situ (11) conservation efforts. Between 1998 and 2001, an experimental reintroduction program established a new population in a 2,000-hectare wetland near the Jataí Ecological Station (EEJ) in Luis Antônio, São Paulo, Brazil. Over time, this population reached a carrying capacity of 25 individuals but experienced genetic diversity loss. To address this, we conducted an embryo transfer experiment using a female from the reintroduced population as a receipt for embryos from the captive population. The female, captured during late pregnancy, was subjected to estrous cycle synchronization for embryo transfer after giving birth and being apart from its fawn. Two embryos from a captive population were implanted, and the female was re-released after 10 days. Monitoring was conducted via radio transmitter collar (GPS–GSM) and helicopter tracking.ResultsThe female did not give birth to the implanted embryos but was recaptured nine months later for an ultrasonographic evaluation, which indicated a six-month pregnancy. This suggests that the implanted embryos were lost early in gestation, but natural fertilization occurred approximately three months post-release.DiscussionThis study demonstrates the technical feasibility of embryo reintroduction as a genetic rescue strategy, even though pregnancy was not carried to term. The ability to capture, temporarily hold, and successfully reintroduce a free-ranging female suggests minimal disruption to natural behaviors. Future improvements in embryo quality, hormonal protocols, and pregnancy confirmation prior to release could enhance the success rate of this method. Embryo reintroduction presents a promising alternative to traditional reintroduction methods, offering a novel approach to mitigating genetic risks in small, isolated populations.